2020
DOI: 10.1111/ppl.13150
|View full text |Cite
|
Sign up to set email alerts
|

The effects of putrescine pre‐treatment on osmotic stress responses in drought‐tolerant and drought‐sensitive wheat seedlings

Abstract: Recent studies have demonstrated that exogenous polyamines have protective effects under various stress condition. A broader understanding of the role of the polyamine pool fine regulation and the alterations of polyamine‐related physiological processes could be obtained by comparing the stress effects in different genotypes. In this study, the impact of pre‐treatment with putrescine in response to osmotic stress was investigated in the drought‐tolerant Katya and drought‐sensitive Zora wheat (Triticum aestivum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 55 publications
2
10
0
Order By: Relevance
“…Previous studies have shown that treatment with the same concentration of different PA compounds may have either positive or negative effects, depending on the PA applied (Put, Spd or Spm), on the mode of PA treatment, on the investigated plant species and on the stress factor, suggesting that “the more PA the better” is not always true [ 48 , 49 , 50 , 51 , 52 ]. Our research results showed that the period between the 9th and 11th days was key for the transformation of EC into GE, in which Put and Spm treatment promoted the transformation, while Spd treatment inhibited it in the early stage, and D-arg, as an inhibitor of PA biosynthesis, also inhibited this process.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that treatment with the same concentration of different PA compounds may have either positive or negative effects, depending on the PA applied (Put, Spd or Spm), on the mode of PA treatment, on the investigated plant species and on the stress factor, suggesting that “the more PA the better” is not always true [ 48 , 49 , 50 , 51 , 52 ]. Our research results showed that the period between the 9th and 11th days was key for the transformation of EC into GE, in which Put and Spm treatment promoted the transformation, while Spd treatment inhibited it in the early stage, and D-arg, as an inhibitor of PA biosynthesis, also inhibited this process.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying measures to alleviate drought stress in grapevine is an urgent concern for both grape growers and wine producers. PAs play diverse roles in responses to drought stress stimulation in plants ( Zhang et al, 2018 ; Doneva et al, 2021 ). The effect of exogenously applied Put and its drought tolerance mechanisms were investigated and confirmed in the current as well as the previous study, where the PAs and redox homeostasis mitigated environmental stresses ( Li et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The lowest leaf temperature could be used as an indicator of plant water status and a possible mechanism of stress avoidance. The lowering leaf temperatures could be due to an increased root suction power, allowing plants to absorb water and transpire it, thereby cooling their leaves (El-Gammaal, 2018, Doneva et al, 2021and Takashima et al, 2021. Similar results were reported by Zada et al ( 2020) who stated that drought stress condition considerably reduced the leaf potential and relative water content and transpiration rate with an associated raised in leaf temperature.…”
Section: Discussionmentioning
confidence: 99%